How We Got Here: A Contextual Review of the Better Access Initiative - Adrian Holmes; Carol Windsor; Clint Douglas (Psychotherapy and Counselling Journal of Australia)
This article presents a contextual review of the literature on mental health policy in the global and Australian settings. The review constitutes an analysis of, firstly, the relevant global literature on mental health policy and practice concepts and, secondly, the Australian literature on mental health policy with a particular focus on the Better Access initiative. Finally, the review offers an analysis of the most recent Better Access evaluation and concludes by considering future directions for the initiative.